Implementasi Program Wisata Sungai Di Kawasan Pasar Sekanak Palembang - Anggraini, Dian; Astari, Nyimas Ulfah (Jurnal Publisitas, 2020)
The city of Palembang has many potential to be developed into a city of river-based historical and cultural tourism. One of the potential tourist attractions of the river is in The Pasar Sekanak, which flows through Sekanak River and in this area there are many heritage buildings. The potential contained in this area has not been seen supported by facilities to develop more optimally into a tourist area. Paying attention to this condition, the Palembang government through Dinas Pariwisata implemented a river tourism program with any problems in this implementation. The purpose of this study is to analyze the implementation of The River Tourism Program in the Pasar Sekanak as well as the factors that drive and inhibit the implementation of the program, achieved by using qualitative descriptive research methods. Data collection techniques, observation, interview and documentation. Research informants came from relevant stakeholders, namely the Palembang city tourism office, the surrounding community and 28 ilir sub-district Palembang. The result showed that the implementation of the river tourism program in The Sekanak market area is a program that refers to RIPPARNAS in 2010-2025, in the development of this region there are obstacles to lack of communication between stakeholders, lack of facilities and infrastructure for tourism support and still lack of professional human resources.